A lumped electro-thermal model for Li-ion cells in electric vehicle application - Makinejad, Kamyar (2020)
A lumped Electro-thermal model of a large format high power Li-Ion cell is introduced in this paper. The model is able to meet the real time implementation requirements; hence it finds its application in Battery Management System (BMS) of an Electric Vehicle (EV). The model is evaluated in Hardware in the Loop (HIL) setup to verify online estimation of cell surface and internal temperature estimation for an on-board EV application. In this study, the cell is considered as a single homogeneous layer and the heat is generated in the centre point of the cell and flows in one direction towards the surface. For this modelling purpose, reversible and irreversible heat in the cell is considered. Irreversible heat consists of the Joule heating effect due to internal resistance of the cell, for instance these values are then calculated with sufficient electrical cell model and evaluated both offline and in real time calculation. Reversible heat is a result of entropy effect which can be negative or a positive value depending on the direction of current flow during charging and discharging process of the cell. Other heat transfer mechanism such as conductive heat transfer and convective heat transfer are also included into the model. This paper introduces a reference case test used to calculate the required necessary coefficients both for parameterization of electrical model and thermal model. The battery setup in the laboratory for measuring the cell surface temperature as reference data as well as cell sandwich setup for evaluating the internal temperature of the cells is explained in detail. Fundamental equations to develop the thermal model are introduced and the model is evaluated in both offline and real time mode.